STRATEGI PEMBELAJARAN GURU DALAM MENGATASI KESULITAN MEMBACA PADA PESERTA DIDIK DISLEKSIA - Atika Ulfah Suroya; Devi Wahyu Ertanti; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
At mi al-hasib school in grade 4 there are children who have difficulty reading, it is known that the child often reversely mentions the letter u with n or b with d, reading consonant alphabet last  is also difficult, and spell from one letter to the next letter is also long time. This problem of course the teacher needs to handle it, because this is also the duty of a teacher. Therefore, teachers need to create learning strategies to help deal with the difficulties of these learners and their causative factors. At that time also the state of the school needs to hold physical distencing due to the covid-19 pandemic, so that teaching time becomes quite limited. Knowing this the presence of researchers is very important because researchers are the main instruments and tools for collecting data. As a data gathering tool researchers collect data with observation, interview, and documentation, namely, observing the situation on the ground directly and conducting interviews for additional data and documentation as supporting evidence. The data collection carried out by researchers get several results including teachers doing learning strategies from making RPP, learning implementation that takes place accompanied by the addition of special learning for learners who have difficulty reading, and conducting learning evaluations. It is also known that the characteristics of the child include dyslexia and the factors due to the lack of parental attention and emotional conditions that are difficult to control. Keyword: Strategies, difficulty reading, disleksia.